2022
DOI: 10.3390/metabo12030272
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Sensitive Quantification of AccQ-Tag Derivatized Amino Acids and Biogenic Amines by UHPLC-UV Analysis from Complex Biological Samples

Abstract: Metabolomic analysis of different body fluids bears high importance in medical sciences. Our aim was to develop and validate a fast UHPLC-UV method for the analysis of 33 amino acids and biogenic amines from complex biological samples. AccQ-Tag derivatization was conducted on target molecules and the derivatized targets were analyzed by UHPLC-UV. The detection of the analytes was carried out with UV analysis and by Selected Reaction Monitoring (SRM)-based targeted mass spectrometry. The method was validated ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The chromatographic standards were prepared in milli-Q filtered water at a final concentration of 10 and 5 ppm, except tryptophan, which was 200 and 100 ppm. The calibration curves were prepared from the stock solutions through serial dilutions [ 94 , 95 ].…”
mentioning
confidence: 99%
“…The chromatographic standards were prepared in milli-Q filtered water at a final concentration of 10 and 5 ppm, except tryptophan, which was 200 and 100 ppm. The calibration curves were prepared from the stock solutions through serial dilutions [ 94 , 95 ].…”
mentioning
confidence: 99%
“…Based on the I AA /I IS and the concentration of internal standard, the concentration of the 10 target AAs can be calculated. Table S3 shows the concentrations (mean ​± ​SD) of serum free AAs from 30 healthy individuals detected by the colloidosomes coupled MALDI-TOF MS, which are all close to the reference concentrations of AAs in healthy adults [ 27 ]. Such a result indicated that the colloidosomes coupled MALDI-TOF MS can accurately quantify AAs in serum.…”
Section: Resultsmentioning
confidence: 95%
“…Supernatants of the cells were collected at the end of the differentiation process and examined as previously described [Guba et al ., 2022; Nokhoijav et al ., 2022]. Briefly, the media were filtered using a 3 kDa filter (Pall Corporation, Port Washington, NY, USA) and 10 µl of this filtrate was derivatized with AccQ·Tag Ultra Derivatization Kit (Waters, Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%